Study of Antidepressant, Anxiolytic, Sedative-hypnotic, and Anticonvulsant Activities of Haplophyllum acutifolium (DC.) G.Don Aqueous Extract in Mice - Seyedali Hashemi; Elnaz Ghorbani; Marjan Talebi; Mona Khoramjouy; Noushin Nikray; Babak Gholamine; Shamim Sahranavard; Mehrdad Faizi (Traditional and Integrative Medicine, 2025)
In traditional Persian medicine, Haplophyllum acutifolium (DC.) G.Don has been utilized as a treatment for central nervous system (CNS) disorders with sedative-hypnotic effects, as recommended by Avicenna. This plant is recognized for its pharmacological characteristics stemming from the existence of various bioactive compounds including alkaloids, coumarins, flavonoids, and lignans. However, a comprehensive investigation of the sedative-hypnotic, anxiolytic, antidepressant, and anticonvulsant activities of H. acutifolium extracts has yet to be conducted. The present investigation aimed to assess the sedative-hypnotic, anxiolytic, antidepressant, and anticonvulsant potential of various extracts obtained from H. acutifolium in NMRI and Swiss mice. Total of 250 mice randomly distributed into specific groups based on the test type. The sedative-hypnotic, anxiolytic, antidepressant, and anticonvulsant properties of extracts of H. acutifolium were assessed using various tests, including open field, the pentobarbital-induced sleep, elevated plus maze, forced swimming, maximal electroshock, and pentylenetetrazol tests. Aqueous, methanol and dichloromethane extracts were administrated intraperitoneally at doses of 50, 100, 200 and 400 mg/kg. Additionally, the concentration of quercetin in H. acutifolium aqueous extract was determined using reversed-phase high-performance liquid chromatography (RP-HPLC). Total phenolic (TPC) and flavonoid contents (TFC) were assessed by spectroscopic methods as well. Upon behavioral tests, it was found that the aqueous extract has the biggest sedative-hypnotic, anxiolytic, antidepressant, and anticonvulsant effects. TPC and TFC of H. acutifolium hydrolyzed aqueous extract were measured as 61.48 ± 2.34 mg GAE/g and 21.13 ±  3.15 RE/g respectively on the basis of colorimetric findings. The RP-HPLC analysis revealed the average quercetin content of 49.87 ± 0.24 mg/100 g dry matter in the aqueous extract. The findings provide a reliable approach for measuring the quantity of quercetin existing in hydrolyzed H. acutifolium aqueous extract, as well as its neuropharmacological effects.